Sharing Individual-Level Health Research Data: Experiences, Challenges and a Research Agenda - Phaik Yeong Cheah (2018)
© 2017, The Author(s). Since January 2016, the Mahidol Oxford Tropical Medicine Research Unit (MORU) has trialled a data-sharing policy where requests to access research datasets are processed through a Data Access Committee. In this paper, we share our experiences establishing data management systems and data-sharing infrastructure including a data-sharing policy, data access committee and related procedures. We identified a number of practical and ethical challenges including requests for datasets collected without specific or broad consent to data sharing and requests from pharmaceutical companies for data to support drug registration applications. We also encountered significant resource constraints which required the development of appropriate human resources and infrastructure. We suggest a research agenda to promote responsible and equitable data sharing while safeguarding the rights and interests of research participants and researchers.